Combined Administration of (R)-Ketamine and the mGlu2/3 Receptor Antagonist LY341495 Induces Rapid and Sustained Effects in the CUMS Model of Depression via a TrkB/BDNF-Dependent Mechanism - Anna Rafało-Ulińska; Piotr Brański; Agnieszka Pałucha-Poniewiera (Pharmaceuticals, 2022)
Ketamine is an effective, rapid-acting antidepressant drug (RAAD), but it induces side effects. To overcome these challenges, attempts have been made to use safer enantiomer ((R)-ketamine) or mGlu2/3 receptor antagonists, which induce ketamine-like effects and enhance its action. Here, we propose combining these two strategies to investigate the antidepressant-like effects of low doses of two ketamine enantiomers in combination with a low dose of the mGlu2/3 receptor antagonist LY341495. Rapid and sustained antidepressant-like effects were assessed in C57BL/6J mice using the tail suspension test (TST) and the chronic unpredictable mild stress (CUMS) model of depression in stress-naïve mice. ELISA was used to measure BDNF levels. In the TST, low doses of both (S)-ketamine and (R)-ketamine were potentiated by a subeffective dose of LY341495. However, in the CUMS model, only (R)-ketamine was able to induce long-lasting anti-apathetic and anti-anhedonic effects when coadministered with low-dose LY341495. The mechanism of this drug combination was dependent on BDNF and AMPA receptor activity. ELISA results suggest that the hippocampus might be the site of this action. MGlu2/3 receptor antagonists, in combination with (R)-ketamine, may serve as potential RAADs, with a high efficiency and low risk of side effects.